Effect of crop rotation on grain yield and on the severity of wheat root diseases, under no-tillage system - dos Santos, Henrique Pereira; Fancelli, Antonio Luiz; Reis, Erlei Melo; Lhamby, Julio Cesar Barreneche (Pesquisa Agropecuaria Brasileira, 1995)
During five years, at the Cooperativa Agrária Mista Entre Rios Ltda., in Guarapuava, PR, Brazil, the effects of some crop rotation systems on grain yield and on the severity of wheat root diseases were assessed. Four rotation systems for wheat were studied: 1) monoculture; 2) rotation of one winter without wheat: 3) rotation of two winters without wheat; 4) rotation of three winters without wheat. A randornized complete block design with four replications and plots with 60 m2 was used. The severity of wheat root diseases in monoculture (33 %), under no-tillage, was higher than the one found in rotation with one (12 %), two (9 %), and three winters wheat (11 %).